Bird community recovery following removal of an invasive tree. Issue 2 (10th June 2021) - O'Leary, Benjamin A.; Burd, Martin; Venn, Susanna E.; Gleadow, Roslyn M.
Abstract: Faunal responses to plant invasions and their managed removal can expand our understanding of the nature of disturbance and the success of restored plant communities. We examined how bird communities responded to the presence and removal of the invasive understorey tree Pittosporum undulatum Vent. (sweet pittosporum) in matched woodland areas in temperate south‐eastern Australia that were free of P. undulatum invasion, were invaded, or had been cleared up to 14 years prior to our sampling. Overall bird species richness and individual abundance were insensitive indicators, as neither were significantly affected by the presence or removal of P. undulatum . However, richness and abundance were sharply lower in and beneath the P. undulatum canopies compared to the forest overstorey, pointing to a large structural modification by the invader. Bird community composition changed in fairly consistent ways at multiple sites upon invasion by P. undulatum, changes that were partly but not completely reversed by removal of P. undulatum . The suite of functional traits of the birds present at the sites was disrupted in idiosyncratic ways at sites invaded by P. undulatum and only very weakly restored upon clearing of P. undulatum . Functional and diversity indices are dependent on the type of management implemented. We propose that a more nuanced approach to management such that some of the invaded forest in neighbouring areas is retained while new trees become established in the cleared areas, providing access to suitable habitat for birds during the transition phase. Such measures are challenging in terms of management and funding but are necessary to maintain avian diversity during and after restoration processes. Abstract : Density and species richness of birds increases with time after the removal of the invasive tree Pittosporum undulatum, but care needs to be taken to provide habitat for vulnerable species such as the Powerful Owl during the transition from one vegetation type to another.